Development of Interactive Online Disability Equality Training (E-DET) to promote inclusiveness in society / Lily Azura Shoaib ... [et al.] - Shoaib, Lily Azura; Mohamed Rohani, Maryani; Mohd Nor, Nor Azlida; Abu Hassan, Muhammad Firdaus (2021)
The global COVID-19 pandemic has forced technology to be integrated in education, and the Disability Equality Training (DET) for dental students was no exception. DET is a part of the Special Care Dentistry (SCD) integrated module teaching activity in the General Dental Practice course for dental undergraduates University Malaya (UM). Dental students were trained to manage dental health for people with disabilities, as well as other medical conditions in SCD. Hence, DET is carried out to promote inclusiveness in society and inculcate positive awareness towards people with disabilities (PWD). Additionally, the training facilitates dental students to become agents of change in developing a more inclusive and enabling society. Thus, this project aimed to develop the facilitator’s guidebook and redesign conventional DET into interactive online DET (e-DET) for dental students. The module content was developed based on the DET framework with modification to suit the application to dental practice. The facilitator’s guidebook provided background, learning objectives, the conduct of e-DET and the role of the facilitator to assist in programme implementation. The e-DET was implemented into three separate online sessions for the Year 3 dental students with designated facilitators. Implementation of activities was via Google slides with Pear Deck for disability seminar, e-DET forums with PWD in Microsoft Teams, and production of disability awareness videos by dental students on YouTube. Facilitators reported on the practicality of the guidebook and most students expressed positive learning experience feedback on e-DET. Improvement in dental students' understanding was reflected concerning the environmental and social barriers PWD may encounter in dental practices. In general, e-DET is beneficial in safeguarding the sustainability of teaching and learning activities in the new norm.